2018
DOI: 10.1111/cas.13785
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory influence of abundant MFG‐E8 expression by esophageal cancer treated with chemotherapy

Abstract: Milk fat globule‐epidermal growth factor factor 8 (MFG‐E8) is secreted from macrophages and is known to induce immunological tolerance mediated by regulatory T cells. However, the roles of the MFG‐E8 that is expressed by cancer cells have not yet been fully examined. Expression of MFG‐E8 was examined using immunohistochemistry in surgical samples from 134 patients with esophageal squamous cell carcinoma. The relationships between MFG‐E8 expression levels and clinicopathological factors, including tumor‐infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
3
20
1
Order By: Relevance
“…MFG-E8 expression is significantly upregulated in colorectal cancer, oral squamous cell carcinoma, and melanoma, compared with normal tissues [11][12][13]. A previous study found that there was a significantly higher rate of high MFG-E8 expression in the esophageal tumor tissues of patients treated with neoadjuvant chemotherapy (NAC), compared to those not treated with NAC [14]. They also observed the increased expression of MFG-E8 in esophageal cancer cell lines after treatment with chemotherapeutic drugs.…”
mentioning
confidence: 95%
“…MFG-E8 expression is significantly upregulated in colorectal cancer, oral squamous cell carcinoma, and melanoma, compared with normal tissues [11][12][13]. A previous study found that there was a significantly higher rate of high MFG-E8 expression in the esophageal tumor tissues of patients treated with neoadjuvant chemotherapy (NAC), compared to those not treated with NAC [14]. They also observed the increased expression of MFG-E8 in esophageal cancer cell lines after treatment with chemotherapeutic drugs.…”
mentioning
confidence: 95%
“…The implanted AS tumors grew into the dark reddish tumors, and the size of the tumor peaked at 3-4 days after implantation, then it gradually shrunk and disappeared, suggesting that antitumor immunity, including CD8 + T cells might be associated with the rejection of AS tumor in mice. Several studies showed the regulation of antitumor immunity by MFG-E8 [14,23,39]. Jinushi et al reported that MFG-E8 inhibited the vaccination activity of GM-CSF-secreting tumor cells through regulatory T cells (Treg) induction, and that the combination anti-MFG-E8 Ab and chemotherapy enhanced antitumor effector T cells and inhibited Treg [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…A protumoral function of MFGE8 has been documented for severaral types of human cancers, including oral, esophageal, colorectal, breast, bladder, ovarian and prostate carcinoma and melanoma [22][23][24][25][26][27][28][29][30]. It has been reported that MFG-E8 expression increased significantly in colorectal cancer compared with normal mucosa tissues, and high MFG-E8 expression was correlated with lymph node metastasis and shortened overall survivals, suggesting that MFG-E8 could be a prognostic marker for colorectal cancer and overexpression of MFG-E8 might be involved in lymph node metastasis and angiogenesis of colorectal cancer [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…MFG-E8 attenuates inflammation and increases Treg cells, efferocytosis, angiogenesis, allograft tolerance, tumorigenicity, and cancer metastasis [81,82]. Moreover, overexpression of MFG-E8 is negatively associated with prognosis in various cancers including breast, colorectal and esophageal cancers [83][84][85]. According to Yamada et al, MFG-E8 promotes angiogenesis by upregulating the expression of VEGF and endothelin (ET)-1 in bone marrow-derived mesenchymal stromal cells to trigger tumor progression in melanomas [86].…”
Section: Bridging Moleculesmentioning
confidence: 99%